Analysis of Company Competitive Advantage through the Application of Environmental Management Accounting - Mochamad Fahru Komarudin (Mandalika Journal of Business and Management Studies, 2025)
The increasing pressure for businesses to balance profitability with environmental sustainability has placed Environmental Management Accounting (EMA) at the forefront of strategic management tools. EMA is crucial for organizations looking to integrate environmental costs into their financial decision-making, helping them manage resource use, reduce waste, and improve overall efficiency (Vasile & Man, 2012). The purpose of this study is to explore how the application of EMA can enhance a company's competitive advantage, specifically through improved operational performance, regulatory compliance, and reputation building. This research uses a qualitative approach with a literature review to synthesize findings from various studies published in the past five years on EMA and its role in sustainable business practices. The results indicate that companies that implement EMA practices gain competitive advantages by reducing environmental costs, optimizing resource management, and aligning with sustainability objectives. These practices not only help organizations comply with environmental regulations but also enhance their reputation among environmentally conscious consumers and investors. Despite these benefits, challenges such as high initial costs, data collection complexities, and organizational resistance are common hurdles in the implementation of EMA. Overall, this study highlights the importance of EMA as a strategic tool for achieving long-term competitiveness and sustainability.